2022
DOI: 10.1002/dad2.12293
|View full text |Cite
|
Sign up to set email alerts
|

Description of the cross‐cultural process adopted in the STRiDE (STrengthening Responses to dementia in DEveloping countries) program: A methodological overview

Abstract: Cross‐cultural adaptation is an important part of using validated questionnaires across countries and settings. Here we describe the cross‐cultural process adopted in the STRiDE (STrengthening Responses to dementia in DEveloping countries) program. We adopted a cross‐cultural adaptation process including forward translation, back translations, and cognitive interviews of the STRiDE toolkit. In total, 50 older adults and 41 carers across sites in Indonesia and South Africa participated in cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 49 publications
(94 reference statements)
0
15
0
Order By: Relevance
“…This is in line with the notion that LMICs will likely continue to be mostly affected by new cases of dementia, 10 , 24 which has led some countries and institutions to outline regional and national strategies to fight dementia. 3 These initiatives include the Strengthening Responses to Dementia in Developing Countries (STRIDE) network, aiming to develop strategies to fight dementia in LMICs, 25 and Latin American Brain Health Institute (BrainLat) 26 and the Latin American and the Caribbean Consortium on Dementia (LAC‐CD), 27 the latter two aiming to facilitate dementia research in Latin America.…”
Section: Dementia Research In Lmics and Hicsmentioning
confidence: 99%
“…This is in line with the notion that LMICs will likely continue to be mostly affected by new cases of dementia, 10 , 24 which has led some countries and institutions to outline regional and national strategies to fight dementia. 3 These initiatives include the Strengthening Responses to Dementia in Developing Countries (STRIDE) network, aiming to develop strategies to fight dementia in LMICs, 25 and Latin American Brain Health Institute (BrainLat) 26 and the Latin American and the Caribbean Consortium on Dementia (LAC‐CD), 27 the latter two aiming to facilitate dementia research in Latin America.…”
Section: Dementia Research In Lmics and Hicsmentioning
confidence: 99%
“…The cultural, sociological, and linguistic diversity of FS-SSA could contribute to culturally related effects impacting cognitive performance, differences in tests assessing cognitive abilities, and differences in cultural appropriateness of dementia care pathways vis-a-vis the local populations. There is a need to pay particular attention to this under-represented group of Africans, as it has been shown that cross-cultural adaptation is essential in validating dementia diagnostic and therapeutic interventions across countries and settings [38][39][40]. Therefore, existing literature on the epidemiology of dementia and cognitive impairment in FS-SSA must be thoroughly explored to extract critical information to de ne future perspectives on Dementia in Africa.…”
Section: Dementia and Cognitive Impairment Epidemiology In Fs-ssamentioning
confidence: 99%
“…24 All of the instruments used were available in Bahasa Indonesia and were translated and crossculturally adapted. 25,26…”
Section: Measures Dementia Ascertainmentmentioning
confidence: 99%